TMIC-08. IDENTIFICATION OF TUMOR SPECIFIC LYMPHOCYTES IN A MURINE GLIOMA MODEL. (11th November 2019) - Shin, David; Lamba, Nikhil; Flores, Catherine; Divita, Bayli; Wildes, Tyler; Grippin, Adam; Fernandez, Brandon; Dyson, Kyle; Mitchell, Duane
Abstract: INTRODUCTION: One major challenge in the use of immunotherapy for glioblastoma is the identification of tumor specific lymphocytes within the tumor microenvironment. Previous studies in non-glioma cancer models have identified CD39 and PD1 as lymphocyte markers of tumor specificity. In this study, we demonstrate the existence of this specific T cell phenotype and show correlation with anti-tumor activity. METHODS: We implanted KR158B murine glioma cells into right caudate nucleus into yellow fluorescent protein (YFP) interferon-gamma reporter mice for a total of 10 4 cells using stereotaxis. At 4 weeks, mice were sacrificed followed by organ harvest. Samples taken included tumor, cervical draining lymph nodes, spleen, and peripheral blood. These were processed into single cell suspensions and then stained for CD3, CD8, CD39, and PD1. Flow cytometry was performed on a BD FACSCanto II. Gating analysis was performed with FlowJo while data analysis was performed with GraphPad Prism. RESULTS: Gating for CD3 + CD8 + on tumor lymphocytes reveals a significant population of CD39 and PD1 double positive (DP) cells (61.4%) not found in the peripheral organs (< 1.0%). Evaluation of these cells for YFP expression demonstrated significantly greater median fluorescence intensity (MFI) in the DP group as opposed to either of the single positive (SP) or double negative (DN) groups (DP = 225.4, SP-CD39 = 40.54, SP-PD1 = 82.7, DN = 29.5, p < 0.0001). CONCLUSION: Here we demonstrate the existence of a unique phenotype of CD39 + and PD1 + expression on lymphocytes within the tumor microenvironment. These DP cells also had high levels of interferon gamma production compared SP and DN groups. This phenotype is not observed in peripheral circulating lymphocytes. Enrichment for this subpopulation will allow for delivery of purified lymphocyte-based immunotherapy in this murine glioma model.